Exploration of Customer Satisfaction Factors in the use of Maxim Online Transportation: An Empirical Study in the City of Samarinda - Satryawati Satryawati; Hamdani Hamdani; Rangga Aditya; Almasari Aksenta; Syachrul Syachrul; Umi Zunaidah; ST Nurhasanah (CV. Science Tech Group, 2025)
The rapid digitalization of app-based transportation services has transformed urban mobility behaviour, making it increasingly important to understand the factors shaping customer satisfaction within a competitive market environment. This study examines the influence of price, ease of use, customer trust, and customer experience on user satisfaction with the Maxim online transportation service in Samarinda, emphasizing perceived value, risk perception, and the socio-emotional dynamics embedded in service interactions. A quantitative approach was employed through a survey of 100 respondents selected using purposive sampling, and the data were analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination to evaluate the predictive strength of the model. The results reveal that price, customer trust, and customer experience significantly affect satisfaction. In contrast, ease of use does not show a significant effect, although it remains a baseline expectation in digital service ecosystems. The strongest determinants of satisfaction are the perceived fit between price and benefits, users' Trust in safety and reliability, and positive social interactions with drivers. The simultaneous test shows that the four variables collectively explain 52.2% of the variance in customer satisfaction, highlighting its multidimensional nature in digital service evaluation. Overall, the study concludes that satisfaction with Maxim is driven more by perceived value and social-emotional experiences than by technological convenience, offering strategic implications for service enhancement, customer relationship strengthening, and long-term loyalty development.